Dielectric, thermal, and swelling properties of calcium ion‐crosslinked sodium alginate film. Issue 6 (11th July 2013) - Bekin, Seda; Sarmad, Shokat; Gürkan, Koray; Yenici, Gökçen; Keçeli, Gönül; Gürdağ, Gülten
<x xml:space="preserve">Abstract</x> In this study, Ca2+‐crosslinked sodium alginate (SA) gel films (SA‐Ca/SA2‐Ca) have been prepared, and their structural and thermal characterizations were investigated using fourier transform infrared spectroscopy, X‐ray diffraction, differential scanning calorimetry, and thermogravimetric analysis, respectively. Dielectric characterization was performed at room temperature in the frequency range of 12 Hz–100 kHz. The equilibrium swelling value (ESV) of gel films was determined both in distilled water and in 0.1 M sodium chloride (NaCl) solution at room temperature. Sodium alginate films (SA/SA2) were also prepared for use as reference. The effect of the crosslinking of sodium alginate on the dielectric and thermal properties of gel films was investigated by comparing the properties of gel films with those of SA/SA2 films. Although ESV of Ca2+‐crosslinked SA film in distilled water is about 350 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh27g8snz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />gH2O</alternatives>/gpolymer, it decreased into one third in 0.1 M NaCl solution. The crosslinking of SA did not significantly affect the thermal properties, but it decreased the β‐relaxation associated with the polar side groups. Frequency spectra of electric modulus, impedance and Cole‐Cole plots confirmed the higher conductance values of SA‐Ca films at low frequencies than those of SA film due to the presence of by‐product of crosslinking. POLYM. ENG. SCI., 54:1372–1382, 2014. © 2013 Society of Plastics Engineers